THE NOTION OF ‘CONCEPT’ IN CULTURAL LINGUISTICS - Yuldasheva Komila Yunusovna (International Engineering Journal For Research & Development, 2022)
This article deals with the study of the description of the notion of "concept" in linguoculturology and the history of its formation in linguistic science. The purpose of this article is to consider the concept as a basic notion in cultural linguistics. The history of development, analysis of the main directions in the study and research of the structure of the concept are shown. The methods of conceptual analysis, different approaches to the classification of concepts and the notion of "conceptosphere" are also considered.